Hyperbolic realism - Sellami, Samir (Bloomsbury Academic, 2024)
Cover – Contents – Acknowledgments – β) Introduction: Why Long Novels? – Part I – 1 Realism on an Expanded Canvas – Why Study the Real? – New Realism and the Return of Speculative Philosophy – Ontology's Unlikely Friend: Postwar Phenomenology beyond Personal Experience – Marc Richir's Quantum Phenomenology – And Yet Another Return of the Real – The Many Lives of Realism – Concepts of Reality, Possibilities of the Novel – 2 Notes on Hyperbole – The Risky Truth of Hyperbole – The Rare Occurrence of Hyperbole in Literary Criticism – Hyperbole as Figura – Phenomenology's Hyperbole – Hyperphenomena, Hyperobjects – Part II – 3 Abundant Discourses – The Maximalist Novel: Lovers &amp – Haters – Amalfitano's Case for the Long and Difficult Novel – Cruft vs. Craft – 2666 and ATD in the Context of Modern Maximalism – 4 Anthropophagic Intertextuality – Abundant Intertextuality – Pynchon's Reparative Genre-Poaching – Bolaño's Intertextual Name-Dropping – Metabolic Intertextuality, Anthropophagic Form – 5 The Visible and the Invisible – It's Always Night, or We Wouldn't Need Light – Flickering Lights in Otherwise Perfect Darkness – The Visible and the Invisible in Richir and Merleau-Ponty – Santa Teresa as Centro Intermitente of 2666 – Perfect Darkness and Capitalist Sorcery in ATD – 6 Flat Fictionality – Métaphores Filées – A Facilitator of Passages – The Secret Trade of Metaphor – Flat Fictionality – The Dismal Metonymies of the Dead – 7 Sed Tamen Effabor – Practical Disbelief – Extravagant Doubt and the Suspension of Mimesis – Lucretius Reacts to the Myth of the Ineffable – Sin Embargo: Ontological Simulacrum and Hyperbolic Stubbornness – Pynchon's Hyperbolic Carnival – The Penultimate Self-Portrait of Edwin Johns – The Melancholy of Totality – 8 Ekphrasis beyond Imagination.
Description based on publisher supplied metadata and other sources
Keywords: Bolaño; Roberto; Pynchon; Thomas; Realism in literature; Hyperbole in literature; Maximalism (Literature)